Utilitarian Attention by Children with Autism Spectrum Disorder on a Filtering Task. - Brodeur, Darlene A.; Stewart, Jillian; Dawkins, Tamara; Burack, Jacob A. (Journal of Autism & Developmental Disorders, 2018)
The findings are evidence that persons with ASD benefit more than typically developing (TD) persons from spatial framing cues in focusing their attention on a visual target. Participants were administered a forced-choice task to assess visual filtering. A target stimulus was presented on a screen and flanker stimuli were presented simultaneously with or after the target, with varying stimuli onset asynchronies (SOAs). Regardless of SOA, TD children showed the expected distracting effects with slower reaction times (RTs) when flankers were at closer distances from the target. However, children with ASD displayed shorter RTs in the conditions in which the stimuli were presented simultaneously or with a short SOA. These findings are interpreted as reflecting utilitarian attention among children with ASD.